Effectiveness of play and learn strategies on knowledge regarding prevention of child abuse among preschoolers and their mothers at selected Anganwadis of Vijaypur - Kamble, Anita; K., Kavita; Varghese, Aleyamma; Desai, Shrikant (International Journal of Contemporary Pediatrics, 2023)
Background: Abuse, especially of children, is a widespread problem. It is crucial to be aware of the warning signs of child abuse and neglect and take preventative measures. The World Health Organisation estimated that 1 billion children (Aged 2-17 yrs) had been victims of violence in 2017. In 2014, UNICEF said that sexual abuse affected 120 million children worldwide. Mental and physical health may be permanently damaged. Objective was to assess the knowledge and to evaluate the effectiveness of the play and learn strategies (PALS) regarding prevention of child abuse among pre-schooler and their mothers. Methods: This study employed the "One group Pre-test, Post-test" pre-experimental design. Non-probability purposive sampling was used. The sample includes 100 mothers and 100 preschoolers. A pre- and post-test self-administered knowledge questionnaire was employed. Data were examined using descriptive and inferential statistics to meet study aims. Results: Present study indicates considerable pre-test knowledge level (p<0.05) among students. After intervention (Play and learn technique), preschoolers' post-test knowledge score improved to 7.86 from 5.16. The mean post-test knowledge score of mothers was 17.6 following intervention, compared to 5.93 pre-test. Education improves preschoolers' and mothers' post-test child abuse prevention knowledge, according to research. Conclusions: Investigators found toddlers prone to child maltreatment. Play and learn performed well to teach kids about child abuse prevention.